Diseño de equipamiento especializado para la ducha en los baños del Asilo Sagrado Corazón de Jesús para adultos mayores en la ciudad de Ambato - Barba Obando, André Rafael (2024)
This project aims to design specialized equipment for showers in the bathrooms of the Sacred Heart of Jesus Asylum. Currently, several drawbacks are observed related to the bathing activity of older adults, especially in the shower area. These problems arise from the physical limitations of the environment, both for caregivers and for older adults themselves. This situation has caused the activity to represent a risk for those involved, since the lack of adequate equipment, due to the restriction of space, makes the process difficult and leads to considerable physical wear and tear for caregivers, which can affect their health with musculoskeletal injuries. . In this context, the project aims to analyze the best care and transport techniques for older adults and then design specialized equipment that optimizes the available space and facilitates handling during transport and showering. The ultimate goal is to reduce activity times, improve the efficiency of the process and prevent possible injuries to caregivers. Furthermore, this project is seen as an opportunity for innovation for the institution and a possible rethinking of the current use of physical space. To carry out this project, we will seek to collaborate closely with design and physiotherapy professionals. The active participation of the members of the Nursing Home will be crucial to ensure that the proposed equipment comprehensively meets the needs and demands of the environment, thus contributing to improving the quality of life of older adults and optimizing the work of caregivers.